Factor structure of the Maslach burnout inventory: An analysis of data from large scale cross-sectional surveys of nurses from eight countries - Poghosyan, Lusine; Aiken, Linda H.; Sloane, Douglas M. (International journal of nursing studies, 2009)
Job burnout is an important predictor of nurse retention. Reliable and valid measures are required to monitor this phenomenon internationally. To evaluate the applicability of the Maslach burnout inventory (MBI) in international nursing research. Secondary analysis of cross-sectional hospital nurse survey data from eight countries. Hospitals in the U.S., Canada, the U.K., Germany, New Zealand, Japan, Russia and Armenia. 54,738 direct care professional nurses from 646 hospitals in eight countries. Confirmatory and exploratory factor analysis were undertaken to identify the factor structure of the MBI. The internal consistencies of the subscales were investigated. Exploratory factor analysis revealed three factors being extracted from the 22-item Maslach burnout inventory. In nearly all countries the two items (6 and 16) related to the “stress” and “strain” involved in working with people loaded on the depersonalization subscale rather than the emotional exhaustion subscale to which they were initially assigned. The three subscales exhibited high reliability with Cronbach alphas exceeding the critical value of 0.70. The correlation coefficients for the emotional exhaustion and depersonalization subscales were strong and positive. The 22-item Maslach burnout inventory has a similar factor structure and, with minor modifications, performed similarly across countries. The predictive validity of the emotional exhaustion and depersonalization subscales might be improved by moving the two items related to stress and strain from the emotional exhaustion to the depersonalization subscale. Nevertheless, the MBI can be used with confidence as a burnout measure among nurses internationally to determine the effectiveness of burnout reduction measures generated by institutional and national policies.